Can the Basis Lead to Arbitrage Profits on the MISO Exchange? - Jones, Kevin (International Journal of Energy Economics and Policy, 2023)
Previous research has shown the basis contains information about future spot prices in wholesale electricity markets. This paper examines the profitability of a trading rule that utilizes the basis on the Midcontinent Independent System Operator (MISO) exchange. 24 hourly time series regressions across each of MISO’s eight regional hubs are estimated to determine the rule’s effectiveness. 67 of the 192 total regressions yield statistically significant results. The number of significant results as well as the size of the returns tend to be highest during the afternoon through early evening hours, which calls into question the efficiency of the market during peak demand times.